VARIABEL-VARIABEL PSIKOSOSIAL YANG MEMPENGARUHI PILIHAN PERAN GENDER ANAK - , Arundati Shinta, Dra.,MA., Prof. T. Dicky Hastjarjo, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The gender role choice often related with the gender stereotype phenomenon. This kind of stereotype has prioritized one sex, whilst the other sex was ignored. Implication of this gender stereotype was that children would feel competent and limit their potentiality only on certain kinds of knowledge and skills. Their field occupations when they grow up would be more likely to be limited. Based on the social cognitive theory, childrenâs gender role choice was influenced by the gender role socialization. This gender socialization was composed of the external factors (parents, school, peers, and mass media) and internal or psychology factor (childrenâs self regulation). Community socialized the gender role through selecting gender appropriate toy, leisure activity, and motivating children on gendered career aspiration. Objective of this research was to identify the influential variables on childrenâs gender role choice. The dependent variables were the childrenâs gender role choice, childrenâs choice on gendered toys, leisure activity, and career aspiration. The independent variables were the parentâs (mother and father) and teacherâs (female and male) attitude on gender role, childrenâs television idol, peerâs choice on gendered activity, and childrenâs self regulation. Population characteristic was children aged 5-7 years old, grade 1. The sampling technique was the proportional sampling. Those children were recruited from 37 public elementary schools in Yogyakarta and they lived with their biological parents (mother and father). The sample size was 353 children (181 girls, 172 boys). Childrenâs choice on gender role was measured through the toy scale, leisure activity scale, and career aspiration scale. Parentâs and teacherâs attitude on gender role was measured through the OAT-AM (Occupation, Activity, Trait-Attitude Measure) scale short version. Peer influence was measured through the peer choice on gendered activity scale. Mass media influence was measured through the childrenâs television idol scale. The internal factor was measured through the childrenâs self regulation scale. The linier multivariate regression analysis revealed that the childrenâs gender role choice and childrenâs choice on gendered toy were predicted by the parentâs and teacherâs gender stereotype attitude, the stereotyped idol television, the stereotyped peerâs choice on activity, and the childrenâs external self regulation. Childrenâs choice on gendered leisure activity and career aspiration were not predicted by those independent variables. The most potential variables in predicting childrenâs gender role and childrenâs gendered toy selection were the peerâs choice on gendered activity and childrenâs self regulation.